Creep failure characteristics and damage creep model of red layer soft rock based on Perzyna viscoplastic theory - Lei Chen; Jinchi Han; Shuguang Zhang; Jiaxu Jin; Baoxin Jia; Jiashun Liu; Jupeng Tang (Scientific Reports)
Abstract Rock creep is essentially a process of damage accumulation. According to the damage evolution of rock under creep conditions, the TAW2000 triaxial test system is used to carry out triaxial creep test on red layer soft rock taken from Yibo Tunnel in Leshan, Sichuan Province, China, and analyzed the creep deformation rule under different confining pressures. Meanwhile, based on the Nishihara model and Weibull distribution function and Perzyna viscoplastic theory, an improved viscoelastic-plastic creep model which can describe the whole process of rock creep failure was established. The critical point damage variable is defined by dividing the creep stage, so that the acceleration creep start time can be determined more accurately. The results show that: (1) The model curves in this paper fit well with the test data, indicating that Weibull distribution function is feasible to describe rock creep damage, and the accuracy and rationality of the model in this paper are verified. (2) Based on Perzyna viscoplastic theory, a more accurate viscoplastic strain expression was established to describe accelerated creep. (3) By defining the critical point damage variables of different creep stages, the relationship between rock creep deformation and damage can be better reflected, which makes up the shortcoming that Nishihara model cannot describe accelerated creep, and enriches the creep constitutive theory of rock materials.